2020
DOI: 10.1186/s12874-020-01013-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequently repeated measurements -our experience of collecting data with SMS

Abstract: Background: As technology is advancing, so are the possibilities for new data collection methods in research, potentially improving data quality and validity of the results. In Sweden, a system using frequent repeated data collection using text messages, SMS Track, has been used in clinical research for more than a decade. In this paper, compliance with repeated text message questions was examined across five different studies, i.e. if compliance was 1: associated with study-specific factors (age or gender of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Non-specific thoracic spine pain intensity was assessed using a 0–10 point Numerical Rating Scale (NRS) ( 33 ). It was also assessed every day for 7 days following the intervention using a web-based platform (SMS-FACTOR, Infomotiv SASU, France) ( 34 ). Patients answered the following question: “Did you experience any thoracic pain today?” If they answered positively, a second question was sent: “On a 0 to 10 scale, 0 being no pain and 10 being severe pain, how much would you rate this pain today?” and a call was made for any pain above pain at baseline to list any adverse event (such as muscle soreness, increase of pain, stiffness).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-specific thoracic spine pain intensity was assessed using a 0–10 point Numerical Rating Scale (NRS) ( 33 ). It was also assessed every day for 7 days following the intervention using a web-based platform (SMS-FACTOR, Infomotiv SASU, France) ( 34 ). Patients answered the following question: “Did you experience any thoracic pain today?” If they answered positively, a second question was sent: “On a 0 to 10 scale, 0 being no pain and 10 being severe pain, how much would you rate this pain today?” and a call was made for any pain above pain at baseline to list any adverse event (such as muscle soreness, increase of pain, stiffness).…”
Section: Methodsmentioning
confidence: 99%
“…Non-specific thoracic spine pain intensity was assessed using a 0-10 point Numerical Rating Scale (NRS) (33). It was also assessed every day for 7 days following the intervention using a web-based platform (SMS-FACTOR, Infomotiv SASU, France) (34). Patients answered the following question: "Did you experience any thoracic pain today?"…”
Section: Clinical Outcome Measuresmentioning
confidence: 99%
“…Conducting follow-up studies of injured individuals post-discharge is not without challenges, such as participant retention [19] and compliance with data collection protocols [56]. EMA studies have generally shown good retention [35,42] and participant compliance with data collection prompts [52]. However, this review has identified several potential barriers to EMA use, including the acknowledged behaviour-altering effects associated with social desirability bias and the Hawthorne Effect [20,47].…”
Section: Discussionmentioning
confidence: 96%
“…In general, compliance with data collection in prospective studies that have used EMAs has been reported as high [52], and that EMAs can reduce recall bias through using real-time data collection [23,34,47]. While participant responses using EMAs are considered to be more reliable than retrospective studies [22,31,48], several study authors did identify as a potential barrier the reliability of information from participants obtained using EMAs [20,23,27,37,42,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…A strength of the study was the longitudinal design and the follow-up by repeated text messages. Although self-reported sick leave outcomes entail a risk of bias, text messaging has demonstrated high compliance (Axén et al 2020 ), and the response rate was 90.2%. Another strength was the use of measures validated in a Scandinavian setting (Berthelsen et al 2020 ; Sanne et al 2005 ; Wännström et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%